Production of interferon-γ by myeloid cells - fact or fancy? - Bogdan, Christian; Schleicher, Ulrike (Trends in Immunology, 2006)
Myeloid cells are usually viewed as targets rather than producers of interferon (IFN)-γ. However, since 1993 several studies have suggested that macrophages and dendritic cells can also secrete IFN-γ in response to various stimuli, which led to the idea of autocrine myeloid-cell activation in innate immunity. Here, we review this concept in the light of recent findings that illustrate the necessity of specific cell markers, cell purity, sensitive single-cell cytokine detection methods, and of further insights into the developmental origin of myeloid and lymphoid cell lineages. We also discuss the possible function of intracellular IFN-γ in macrophages and the evidence for a protective role of myeloid IFN-γ in vivo. © 2006 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2024-02-26